2007
DOI: 10.1093/carcin/bgm200
|View full text |Cite
|
Sign up to set email alerts
|

NDRG1, a growth and cancer related gene: regulation of gene expression and function in normal and disease states

Abstract: N-myc downstream-regulated gene 1 (NDRG1) is an intracellular protein that is induced under a wide variety of stress and cell growth-regulatory conditions. NDRG1 is up-regulated by cell differentiation signals in various cancer cell lines and suppresses tumor metastasis. Despite its specific role in the molecular cause of Charcot-Marie-Tooth type 4D disease, there has been more interest in the gene as a marker of tumor progression and enhancer of cellular differentiation. Because it is strongly up-regulated un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
145
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(160 citation statements)
references
References 66 publications
3
145
0
4
Order By: Relevance
“…NDRG1, also known as DRG1, CAP43, RIT42, RTP, and PROXY-1, was first described as differentiation-related gene 1 (18,19). NDRG1 encodes the 46-kDa protein, NDRG1, which is highly conserved among multicellular organisms and is ubiquitously expressed in tissues in response to cellular stress (20). Prior studies demonstrated that NDRG1 is necessary but not sufficient for p53-mediated apoptosis (21) and may play a role in spindle organization, as NDRG1 has been shown to colocalize with centrosomes (22).…”
Section: Distinct Phenotypes Of P53 Null Versus P53 R248w Heterozygousmentioning
confidence: 99%
“…NDRG1, also known as DRG1, CAP43, RIT42, RTP, and PROXY-1, was first described as differentiation-related gene 1 (18,19). NDRG1 encodes the 46-kDa protein, NDRG1, which is highly conserved among multicellular organisms and is ubiquitously expressed in tissues in response to cellular stress (20). Prior studies demonstrated that NDRG1 is necessary but not sufficient for p53-mediated apoptosis (21) and may play a role in spindle organization, as NDRG1 has been shown to colocalize with centrosomes (22).…”
Section: Distinct Phenotypes Of P53 Null Versus P53 R248w Heterozygousmentioning
confidence: 99%
“…Hence, NDRG1 is a promising prognostic indicator and molecular target for these cancers (14), which represent some of the most common and fatal neoplastic conditions. The molecular functions of NDRG1 have been the subject of increasing interest in recent years, with studies demonstrating that this metastasis suppressor is involved in numerous signaling pathways that regulate cancer cell proliferation, invasion, angiogenesis, and migration (7,9,14,15). Specifically, NDRG1 inhibited the oncogenic RAS, c-Src, phosphatidylinositol 3-kinase (PI3K), WNT, ROCK1/pMLC2, and nuclear factor -light chain enhancer of activated B cell (NF-B) pathways, while promoting expression of key tumor-suppressive molecules such as phosphatase and tensin homolog, E-cadherin, and mothers against decapentaplegic homolog 4 (SMAD4) (4, 6, 8, 16 -20).…”
mentioning
confidence: 99%
“…Recent studies demonstrated that the NDRG1 gene is controlled by a variety of factors and stimuli related to cancer progression, including oncogenes, tumor suppressors, hypoxic microenvironment, and hormone dysregulation (30,31). Clinical studies also provided compelling evidence that reduced expression of the NDRG1 gene was significantly associated with poor overall survival rate in pancreatic ductal adenocarcinoma, glioma, prostate, breast, and colorectal cancers (32).…”
mentioning
confidence: 99%